Prevalence and Risk Factors of Lumpy Skin Disease in Pakem District, Yogyakarta - Rahmi, Siwi Meylina; Salim, Devi Andreani; Primatika, Roza Azizah; Nugroho, Widagdo Sri; Susetya, Heru; Widiasih, Dyah Ayu; Bawono, Gigih (IPB University, 2025)
Lumpy Skin Disease (LSD) is an infectious dermatological condition affecting ruminant animals, particularly cattle, and is caused by the Lumpy Skin Disease Virus (LSDV). This virus possesses DNA genetic material derived from the Capripoxvirus genus within the Poxviridae family. The World Organization for Animal Health (WOAH) states that LSD has a mortality of 1-5% and a morbidity of 10-20% and can spread quickly if not handled properly. This study aimed to determine the prevalence of LSD and to identify associated risk factors in Pakem District, Yogyakarta. This research used a cross-sectional study. Samples were taken using a double-stage sampling technique with a total sample of 262 cattle. The study employed primary data collected through interviews with farmers. Data was analyzed descriptively and analytically. Data in the form of frequencies and percentages were analyzed using univariate methods. The relationship between risk factors and the incidence of LSD was analyzed using bivariate Chi-Square methods. The results showed that the prevalence of LSD in the Pakem District was 7.6%. The presence of ticks was identified as a risk factor for LSD disease, with a probability value of p<0.05. The association’s strength was indicated by an odds ratio (OR) of 2.64, suggesting that ticks may elevate the risk of contracting LSD by a factor of 2.64. The prevalence of LSD in Pakem District was 7.6%, and the presence of ticks 2.64 times increases the risk of LSD incidents. Control measures can be improved by carrying out livestock management in handling vectors.